Caring for Family Members With Alzheimer’s and Burnout Syndrome: Impairment of the Health of Housewives - Avargues-Navarro, María Luisa; Borda-Mas, Mercedes; Campos-Puente, Alina de las Mercedes; Pérez-San-Gregorio, María Ángeles; Martín-Rodríguez, Agustín; Sánchez-Martín, Milagrosa (Frontiers in Psychology, 2020)
The occupation of housewives may be a psychosocial risk factor leading to situations of chronic stress and burnout. This may be aggravated when they become caregivers for a family member with Alzheimer’s. The burnout syndrome and how it can affect general health and the presence of emotional disorders was studied in housewives who were family caregivers of an Alzheimer’s patient. The sample selected was made up of 193 housewives (96 were also caregivers for a family member with Alzheimer’s). Sociodemographic measures used were, the Maslach Burnout Inventory and The General Health Questionnaire. Burnout was found in a significant percentage of participants. Emotional exhaustion, affectation of general health and presence of emotional disorders were higher in caregivers. Emotional exhaustion, general health and anxiety were more influential while depersonalization affected more the appearance of depressive symptoms. Being a caregiver and emotional exhaustion appeared to be the best predictors of emotional disorders. Prevention programs must therefore be developed and social support policies must be revised for this group